2018
DOI: 10.1002/jocb.240
|View full text |Cite
|
Sign up to set email alerts
|

Application of Latent Semantic Analysis to Divergent Thinking is Biased by Elaboration

Abstract: Scoring divergent‐thinking response sets has always been challenging because such responses are not only open‐ended in terms of number of ideas, but each idea may also be expressed by a varying number of concepts and, thus, by a varying number of words (elaboration). While many current studies have attempted to score the semantic distance in divergent‐thinking responses by applying latent semantic analysis (LSA), it is known from other areas of research that LSA‐based approaches are biased according to the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 79 publications
(115 citation statements)
references
References 48 publications
1
109
0
2
Order By: Relevance
“…In addition, prior research suggests one substantial weakness of applying an additive compositional model in creativity assessment is that it penalizes (i.e., reduces) semantic distance scores for more elaborate creativity responses (Forthmann et al, 2018). We attempt to replicate this finding and determine whether or not multiplicative models similarly penalize semantic distance scores, with the goal of explaining maximal variance in human creativity ratings.…”
Section: The Present Researchmentioning
confidence: 87%
See 4 more Smart Citations
“…In addition, prior research suggests one substantial weakness of applying an additive compositional model in creativity assessment is that it penalizes (i.e., reduces) semantic distance scores for more elaborate creativity responses (Forthmann et al, 2018). We attempt to replicate this finding and determine whether or not multiplicative models similarly penalize semantic distance scores, with the goal of explaining maximal variance in human creativity ratings.…”
Section: The Present Researchmentioning
confidence: 87%
“…Notably, our study used multiplicative models, whereas Dumas and colleagues used additive models, and we found substantially better prediction of human ratings compared to additive models-a finding that replicated in Study 2 and is consistent with recent work comparing additive and multiplicative models in the context of predicting human similarity judgments . In addition, Forthmann et al, (2018) showed that additive compositional models penalize, that is, reduce the semantic distance of longer creative responses, when in fact elaboration should often increase creativity. While removing stop words mitigates this penalty (Forthmann et al, 2018), for the first time, we showed that a multiplicative compositional model reversed the correlation between elaboration and semantic distance: a multiplicative model showed positive correlations between semantic distance and elaboration and an additive model showed negative correlations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations